If one of the roots of the quadratic equation is x2 - (a+6)x +6 =0 is -3. what will be the other root
Answers
Answered by
0
Answer:
Hey mate;
Step-by-step explanation:
x²-(a+6)x+6
p(x)= (-3)²-(a+6)-3+6=0
p(x)= 9+3a+18+6=0
p(x)=33+3a
33+3a=0
3a=-33
a=-33
a=-33/3
a=-11
____________
Now, equation will be;
x²-(-5)x+6=0
x²+5x+6=0
x²+2x+3x+6=0
x(x+2)+3(x+2)
x+3=0, x+2=0
x=-3,-2
______________
Mark brainliest❤
Answered by
0
Answer: MY NAME ABHIJEET
Step-by-step explanation: Step-by-step explanation:
x²-(a+6)x+6
p(x)= (-3)²-(a+6)-3+6=0
p(x)= 9+3a+18+6=0
p(x)=33+3a
33+3a=0
3a=-33
a=-33
a=-33/3
a=-11
____________
Now, equation will be;
x²-(-5)x+6=0
x²+5x+6=0
x²+2x+3x+6=0
x(x+2)+3(x+2)
x+3=0, x+2=0
x=-3,-2
Similar questions